Perception of professional autonomy in Nursing graduates from a private university, Chiclayo 2021 - Muñoz Vasquez, Elizabeth (2023)
Objective: Describe and analyze the perception about professional autonomy in nursing graduates from a private university, Chiclayo 2021. Method: Qualitative research, descriptive design, the sampling was non-probabilistic by snowball, the population was made up of 580 nursing graduates; and the sample was achieved with 12 nursing graduates from the Santo Toribio de Mogrovejo Catholic University who met the established inclusion criteria, determining the size of the sample by saturation and redundancy. The data was collected through a virtual semi-structured interview, validated by expert judgment; taking into account ethical principles and criteria of scientific rigor. Main results: Two categories emerged: I. Scientific knowledge practiced as a means to achieve professional autonomy and II. Independence and responsible freedom, elements, inherent in autonomous care. Overall conclusion: According to the perceptions of the graduates, they maintain an autonomous professional practice, however, they present difficulties caused by the existence of professionals who seek to undermine their freedom to act on their own in carrying out activities that are part of their functions, causing discomfort and discomfort in their work area by having to tolerate these attitudes in order to avoid further conflicts.